“A History of One Happy Marriage”: Discourses of Rehabilitation and Otherness in the Autobiography of Havelock Ellis - Kolářová, Kateřina (Dějiny – teorie – kritika, 2011)
This article raises questions addressing the discursive fabrications of genealogy of sexual deviance and abnormality that rely on metaphors of bodily as well as mental difference. Arguing beyond such prosthetic understanding of relationship between gender, sexual and bodily/mental difference, I propose an intersectional reading accentuating interdependencies of categories of gender, sexuality and disability. I revisit the autobiography of Havelock Ellis, the founder of British sexology, and discuss the role of bodily difference to construe a representation of happy and evolved marriage, while at the same time it allows Ellis to „out“ his rife as a Lesbian. It is, as I argue, discourses of dis/ability and bodily difference that enable to harmonize the seemingly unsurpassable conflicts between homo/heterosexuality into a narrative of a marriage. Lastly, I discuss the discursive figure of rehabilitation (of gender, sexual as well as bodily/mental difference) for its constitutive role for performances of hegemonic masculinity/ies.